Pvp dual function-assited hydrothermal synthesis of Bi2O2CO3 microspheres and their high photocatalytic performance - Chai, Wee Ting (2013)
Monodisperse Bi2O2CO3 nanoplate-assembled microspheres with size of 1 μm have been obtained through a facile hydrothermal treatment, using Bi(NO3)3 and polyvinylpyrrolidone (PVP) as the starting agents. During the reaction process, PVP not only provides C and O sources but also as a template to induce the nanoplate-assembly to form microspheres. Based on the present reaction system, uniform 1-μm-sized Bi2O2CO3 microspheres constructed by nanoplates can be obtained by adding a little amount of KCl. A possible formation mechanism of Bi2O2CO3 microspheres is proposed on the basis of the outcomes of the PVP and time-dependent experiments. As a superior photocatalyst, the 1-μm-sized Bi2O2CO3 microspheres exhibit high photocatalytic activity for the degradation of methyl orange (MO) dye, due to the novel hierarchical morphology and high surface area. Therefore, the as-prepared uniform monodisperse Bi2O2CO3 microspheres with well-defined hierarchical structures are potential candidates in the applications of environment.